Bacteria associated with Haemonchus contortus : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Sinnathamby, Gajenthiran (Massey University, 2012)
Internal parasitism, a major cause of production losses in sheep, is routinely controlled by anthelmintic drenches, however, alternative control strategies are needed to combat the increasing resistance to these chemicals. [sic] A possible novel method of controlling abomasal nematodes, such as Haemonchus contortus, is manipulation of their essential resident bacteria, as is currently used to control filarial nematodes. For the first time, bacteria have been identified in the reproductive tract, as well as in the gut, of H contortus, using genetic fingerprinting, light and electron microscopy and fluorescence in situ hybridisation (FISH). PCR-DGGE analysis showed that adult worms had less complex bacterial profiles than did abomasal contents. L3, eggs and adult worms had similar bacterial profiles; 16S rRNA sequences obtained from seven major common DGGE bands were dominated by lactic acid bacterial and Proteobacterial sequences. PCR-DGGE short sequences and clone libraries of nearly full length sequences from all three life-cycle stages contained sequences belonging to Weissella, Lactococcus, Leuconostoc and Streptococcus. Clone library sequences were used to design group-, class- and species-specific FISH probes to locate bacteria in the parasites. The gut lumen of adult worms contained a mixed population of Grampositive and Gram-negative bacteria, which appeared to be multiple morphotypes in TEM images. The FISH probe (EUB338), which targets most bacteria, hybridised with the gut bacteria, but only some of these were targeted by Strc493, which targets most Streptococcus sp. and some Lactococcus sp. Neither the lactic acid bacterial group- nor the Weissella species-specific probes targeted any bacteria in the gut. A single morphotype of Gram-positive bacteria was seen in large numbers in the distal uterus of female H contortus in the TEM. They were close relatives of either Lactococcus sp. or Streptococcus sp., as they were targeted by the FISH probe Strc493. These bacteria seemed to be non-pathogenic to the nematodes, as adult female worms appeared to be healthy (nonnal in size and active) and carry normal eggs within them. Their roles in worm biology are unknown. A smaller number of bacteria were seen in the TEM in eggs within female wom1s. They were closely related to Weissella confusa, as all were targeted by lactic acid bacterial group- and Weissella species-specific probes, as well as by EUB338. These bacteria were dispersed throughout the eggs, as they could be seen at different focal panels in confocal microscopy. DNA fingerprinting and visualisation of these bacteria in eggs strongly suggest they are maternally transmitted endosymbionts. As this study was carried out on a parasite strain which has been maintained in the laboratory, practical applications of this research would depend on these bacteria being present in field strains of H. contortus.
Keywords: Haemonchus contortus; Internal parasites; Bacteria within parasites; Bacteria